Mitochondrial aconitase and citrate metabolism in malignant and nonmalignant human prostate tissues - Franklin Renty B; Desouki Mohamed M; Singh Keshav K; Costello Leslie C (Molecular Cancer, 2006)
Abstract Background In prostate cancer, normal citrate-producing glandular secretory epithelial cells undergo a metabolic transformation to malignant citrate-oxidizing cells. m-Aconitase is the critical step involved in this altered citrate metabolism that is essential to prostate malignancy. The limiting m-aconitase activity in prostate epithelial cells could be the result of a decreased level of m-aconitase enzyme and/or the inhibition of existing m-aconitase. Earlier studies identified zinc as an inhibitor of m-aconitase activity in prostate cells; and that the depletion of zinc in malignant cells is an important factor in this metabolic transformation. However, a possibility remains that an altered expression and level of m-aconitase enzyme might also be involved in this metabolic transformation. To address this issue, the in situ level of m-aconitase enzyme was determined by immunohistochemical analysis of prostate cancer tissue sections and malignant prostate cell lines. Results The immunocytochemical procedure successfully identified the presence of m-aconitase localized in the mitochondrial compartment in PC-3, LNCaP, and DU-145 malignant prostate cell lines. The examination of prostate tissue sections from prostate cancer subjects demonstrated that m-aconitase enzyme is present in the glandular epithelium of normal glands, hyperplastic glands, adenocrcinomatous glands, and prostatic intraepithelial neoplastic foci. Quantitative analysis of the relative level of m-aconitase in the glandular epithelium of citrate-producing adenomatous glands versus the citrate-oxidizing adenocarcinomatous glands revealed no significant difference in m-aconitase enzyme levels. This is in contrast to the down-regulation of ZIP1 zinc transporter in the malignant glands versus hyperplastic glands that exists in the same tissue samples. Conclusion The results demonstrate the existence of m-aconitase enzyme in the citrate-producing glandular epithelial cells; so that deficient m-aconitase enzyme is not associated with the limiting m-aconitase activity that prevents citrate oxidation in these cells. The level of m-aconitase is maintained in the malignant cells; so that an altered enzyme level is not associated with the increased m-aconitase activity. Consequently, the elevated zinc level that inhibits m-aconitase enzyme is responsible for the impaired citrate oxidation in normal and hyperplastic prostate glandular epithelial cells. Moreover, the down-regulation of ZIP1 zinc transporter and corresponding depletion of zinc results in the increase in the activity of the existing m-aconitase activity in the malignant prostate cells. The studies now define the mechanism for the metabolic transformation that characterizes the essential transition of normal citrate-producing epithelial cells to malignant citrate-oxidizing cells.